STUDY OF THE STRESS-STRAIN STATE OF BUSBAR PUNCHING TOOLS RESTORED BY VARIOUS METHODS - Kassymbabina, Dana; Mussayev, Medgat; Sherov, Karibek; Tolganay, Zhanibek; Donenbayev, Bakytzhan; Karsakova, Nurgul; Kongkybayeva, Arailym; Shezhau, Kadylet (Journal of Applied Engineering Science, 2025)
The aim of this study is a comparative analysis of the stress–strain state of busbar punching tools after restoration using different methods. An overview of existing methods for restoring punches and dies was conducted. The analysis showed that each method has its own advantages and limitations. To address this issue, two restoration methods for the busbar punching tool are proposed: hardfacing of worn and damaged surfaces, and replacement of the working part with an insert made of carbon steel. A numerical simulation using the ANSYS software package was carried out to investigate the stress–strain state of busbar punching tools restored by two proposed methods. The simulation focused on determining the stresses in the working zones of the tool, deformations, and the distribution of contact forces. The results made it possible to identify critically loaded areas of the tool design and evaluate the effectiveness of the proposed restoration and modernization methods. The research, the results of which are presented in this article, is funded by the Committee on Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan (grant № AP19578884 "Increasing wear resistance and improving the design of the tool of the busbar punching machine").